文学律法的伦理光照:卡夫卡《审判》新论. - Liao Yi (Foreign Literature Studies, 2015)
We can really see through literature law behind positive law and another trial behind The Trial by the method of macroscopic interpretation and microscopic analysis to integrate Kafka’s social cultural environment, unique way of thinking, legal experience and activation of specific events in the background. Kafka tried to penetrate the essence of law in The Trial from the point of theme. Through a literary inquiry into the nature of law, literature law that is identified by Kafka becomes the mysterious source code beyond the positive law. In terms of its basic features, Kafka’s literary law has its unique paradigm, clear principle, open structure and pluralistic interpretation. In The Trial, literature ethics is the real "trial" as closer to the truth.Literary jurisprudence in the future should go beyond the movement of "law and literature"